Application of Grey Relational Analysis for Optimization of Kerf quality during CO2 laser cutting of Mild Steel. (2018) - Karthikeyan, R.; Senthilkumar, V.; Thilak, M.; Nagadeepan, A.
Abstract: Laser cutting process is a thermal based unconventional machining process used to cut different engineering materials of various complex shapes. The cut edges, top kerf, bottom kerf and kerf ratio are greatly affected by laser power, cutting speed, gas pressure, nozzle position and properties of the work piece. In this investigation CO2 laser cutting of mild steel has been attempted to minimize the kerf width and kerf ratio. The box-behnken design was used to carry out the experiments by considering cutting speed, power and gas pressure as the input parameters. The obtained experimental data was applied in grey relational analysis and grey relational grade was calculated to find the significant contribution of each parameter and to predict the optimum parameters for minimum kerf quality as well. From the results it was found that power was the most significant factor as compared to other factors and the optimum condition was 1 kW of power, 1.3 m/min of cutting speed and 0.15 bar of gas pressure.